2019
DOI: 10.3390/pharmaceutics11120671
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamer Hydrogels for Biomedical Applications

Abstract: This review article focuses on thermoresponsive hydrogels consisting of poloxamers which are of high interest for biomedical application especially in drug delivery for ophthalmic, injectable, transdermal, and vaginal administration. These hydrogels remain fluid at room temperature but become more viscous gel once they are exposed to body temperature. In this way, the gelling system remains at the topical level for a long time and the drug release is controlled and prolonged. Poloxamers are synthetic triblock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(182 citation statements)
references
References 109 publications
(113 reference statements)
0
182
0
Order By: Relevance
“…Poloxamers are biodegradable by erosion [57] and biocompatible polymers [58]. Based on these safety data and the information that the manufacturing process can be controlled to limit unwanted impurities, the Cosmetic Ingredient Review Expert Panel concluded that poloxamers are safe as used [59].…”
Section: Preparation Of In Situ-forming Gelmentioning
confidence: 99%
“…Poloxamers are biodegradable by erosion [57] and biocompatible polymers [58]. Based on these safety data and the information that the manufacturing process can be controlled to limit unwanted impurities, the Cosmetic Ingredient Review Expert Panel concluded that poloxamers are safe as used [59].…”
Section: Preparation Of In Situ-forming Gelmentioning
confidence: 99%
“…Temperature‐responsive hydrogels can respond to external temperature stimuli and alter their structural or other properties depending upon environmental changes; thus, these materials are vastly promising for various applications, such as controlled drug delivery, sensors, and tissue engineering (Russo & Villa, 2019). In addition, temperature‐responsive hydrogels are suitable for biological applications because they can generate a remarkably rapid response to biological temperatures, they are convenient and quick, and they cause minimal damage to biological specimens and living tissues (Klouda, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Poloxamers or Pluronics ® are a class of water-soluble, non-ionic, triblock copolymers, composed of a central poly(propylene oxide) (PPO) block and two terminal poly(ethylene oxide) blocks [181]. A wide range of poloxamers is commercially available with varying block molecular weights.…”
Section: Ionotropic Gelation With Other Polymersmentioning
confidence: 99%
“…Poloxamers can form thermoreversible gels in aqueous solutions, generally around 37 • C, and they have attracted growing interest as carriers for bioactive compounds and other biomedical applications [181]. Nevertheless, the poor mechanical properties are a major drawback of pure poloxamer gels.…”
Section: Non-ionic Polymersmentioning
confidence: 99%